IMPORTANT METHODS OF ATTRACTING THE ATTENTION OF PRIMARY SCHOOL STUDENTS - Shukurova H.S.; Begimova Nozima Akram qizi; SH. M. Mirziyoyev (Galaxy International Interdisciplinary Research Journal, 2021)
This article provides methodological tips for engaging primary school students.